Formation of the calcarine sulcus: a potential marker to predict the progression in utero of isolated mild fetal ventriculomegaly. Issue 28 (July 2017) - Li, Hehong; Liu, Guangjian; Lin, Fangqin; Liang, Huiying
Abstract : Abstract: Our previous study confirmed the negative association between the development of calcarine sulcus and the width of lateral ventricles. The purpose of current study was to evaluate the reliability of calcarine sulcus depth in the 2nd trimester to predict the prenatal enlargement of lateral ventricle in fetuses with isolated mild fetal ventriculomegaly (IMVM). This study used a retrospective cohort study design. A total of 97 pregnant women with IMVM diagnosed between 20 and 26 weeks' gestation returned for a 2nd examination at 30 to 32 weeks. Lateral ventricular size and calcarine sulcus depth were acquired from ultrasonography and magnetic resonance imaging (MRI) scans, respectively. Progression was defined as the process of developing from a lower group toward a higher (<10 mm, 10–12 mm, 13–15 mm, and ≥16 mm). Significant correlation was observed between calcarine sulcus depth and ventricular measurements at the 2nd scan ( r  = −0.71, P  < .0001). Receiver-operating characteristic curves showed that calcarine sulcus depth (area under curve [AUC] = 0.83, 95% confidence interval [CI] = 0.74–0.92) had the best diagnostic performance in predicting the prenatal progression, as compared with lateral ventricle width (AUC = 0.69, 95%CI = 0.54–0.84) and gestational age (AUC = 0.70, 95%CI = 0.57–0.83) at the initial scan. The cutoff value for calcarine sulcus depth was 3.3 mm, with the corresponding sensitivity and specificity were 75.0% and 81.3%, respectively. Multivariate analyses showed that calcarine sulcus depth ≥3.3 mm (odds ratio = 0.09, 95%CI = 0.02–0.38, P  = .001) was an independent predictor of the prenatal progression. For IMVM, calcarine sulcus depth might be a powerful marker to identify subjects at higher risk for worse prenatal progression.